Pembelajaran Augmentasi Reality untuk Meningkatkan Pemahaman Hakikat Sains Sistematis Literatur Review - Elza Ardea Nadela; Niki Dian Permana; Mery Berlian; Rian Vebrianto (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Students' ignorance of science makes it difficult for educators to teach. Augmented Reality can help students and instructors complete the learning system. Truth enhancement is an innovation that incorporates 3D (3D) virtual items in a real 3D climate. The survey results show that in the learning process the students' lack of interest in learning. The lack of student interest in carrying out the learning process is caused by learning activities carried out only by the lecture method and giving questions on a regular basis. This research is intended as a training aid to help students attract more attention and interest in the learning process. AR innovations have been applied in various fields and in various areas of training. In the field of training, the extension of truth is used as a learning climate. The innovation of increased reality can also be utilized to understand scientific ideas by describing the construction of model items and theoretical ideas. The method used is a systematic literature review using PRISMA diagrams and using two digital libraries, namely Google Scholar and Google Scholar. So that the selected literature is relevant, the search uses the keywords